2015
DOI: 10.1200/jco.2015.33.3_suppl.294
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor-infiltrating lymphocytes (TILs) and expression of PD-L1 in cholangiocarcinoma.

Abstract: 294 Background: Cholangiocarcinoma is a malignancy arising from the epithelial cells of the biliary tract with poor prognosis. Tumor-infiltrating lymphocytes (TILs) have a prognostic impact in various solid tumors. We aimed to investigate TIL expression and programmed cell death ligand PD-L1 and their clinical relevance in cholangiocarcinoma. Methods: Formalin-fixed paraffin-embedded tumor samples from thirty seven patients with resected and histologically verified cholangiocarcinoma between 1990 and 2011 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…PD-L1 expression is found in a number of GI tumour types, suggesting this may be a possible biomarker [7,17,30,[37][38][39][40][41][42][43]. However, although PD-L1 expression on IHC has been correlated with prognosis and response in several studies [2,[7][8][9]30,37], other studies demonstrated efficacy in patients deemed PD-L1 negative [44], therefore the true relationship between PD-L1 expression and outcome is yet to be established.…”
Section: Pd-l1 Expressionmentioning
confidence: 89%
See 3 more Smart Citations
“…PD-L1 expression is found in a number of GI tumour types, suggesting this may be a possible biomarker [7,17,30,[37][38][39][40][41][42][43]. However, although PD-L1 expression on IHC has been correlated with prognosis and response in several studies [2,[7][8][9]30,37], other studies demonstrated efficacy in patients deemed PD-L1 negative [44], therefore the true relationship between PD-L1 expression and outcome is yet to be established.…”
Section: Pd-l1 Expressionmentioning
confidence: 89%
“…One possible antibody for detecting PD-L1 expression on IHC is the murine antihuB7-H1, clone 5H1 (mAb5H1) [2,43]. This antibody can detect the PD-L1 (B7-H1) protein on the cell surface of frozen tissue sections [8,47].…”
Section: Antibody Choicementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that the activity of PD-1 and/or PD-L1 was associated with patients' prognoses [18][19][20], but others could not validate the significance [21,22]. Until now, in bile duct cancer, two published studies and one abstract have analyzed the immunohistochemical results of PD-1 and/or PD-L1 [23][24][25]. However, the role of the immune checkpoint in patients' prognoses is not known yet.…”
Section: Introductionmentioning
confidence: 92%